A New Species of Predatory Mite, Amblyseius (Acarina: Phytoseiidae) from Stored Coffee Berries - Sadanandan, Mary Anithalatha (Journal of Bio-Science, 2007)
A new species of predatory mite of the family Phytoseiidae viz., Amblyseius (Amblyseius) coffeae sp. nov. is described from stored coffee berries. Key words: Predatory mite; Phytoseiidae; Amblyseius; new species J. bio-sci. 14: 39-41, 2006